Burial traditions in early Mid-Holocene Island Southeast Asia: new evidence from Bubog-1, Ilin Island, Mindoro Occidental - Pawlik, Alfred (Archīum Ateneo, 2019)
The Bubog-1 rockshelter on Ilin Island has provided important evidence for Late Pleistocene to Mid-Holocene (c. 33 000–4000 cal BP) human habitation, yet little is known about the contemporaneous transmission of material culture, technology and mortuary practices across Island Southeast Asia. Recent archaeological research at Bubog-1 has revealed a tightly flexed inhumation dating to c. 5000 cal BP—a type representative of a widespread, contemporaneous burial practice observed across the region. The emergence of diverse burial practices and their spread across Island Southeast Asia coincides with evidence for technological innovation and increasing long-distance interaction between island communities.